Suscetibilidade a inseticidas, análise do gene Kdr (knockdown resistance) e de enzimas de detoxificação no mecanismo de resistência, em populações de Aedes aegypti da cidade de Manaus - Silva, Eliane Christine Santos (2012)
Continued use of chemical pesticides and has led population to intense selection pressure, causing problems for vector control programs. Resistances Kdr (Knockdown resistance) have been reported in several locations in Brazil and other tropical and subtropical areas of the world, characterized by changes in sodium channel of insects, causing loss of coordination, after exposure to the insecticide, with recovery its effect often caused by recessive mutations, among which, Val1016Ile, located on voltage-gated sodium channel mosquito species A. aegypti (AaNav), dengue vector. This study aimed to evaluate the susceptibility of third instar larvae to the insecticide temefós, formulation ABATE 1G and adults, deltamethrin, and determining esterase activity, phosphoglucomutase and hexokinase, and the presence of the mutation Val1016Ile in four A. aegypti populations Manaus / AM, submitted and not submitted to insecticides. Were analyzed by means of bioassays of insecticide susceptibility, neighborhoods A. aegypti populations: Alvorada I, Coroado I, Monte das Oliveiras and Praça 14 de Janeiro, in decreasing order to estimate mortality rates, using the diagnostic doses of ABATE 1G (0.012 mg / L) and deltamethrin (5μg). With the results of bioassays were identified Praça 14 and Alvorada I populations like being the more resistant, and Coroado I and Monte das Oliveiras, less resistant. Unable to associate the esterase activity with resistance to organophosphate temephos, nor to deltamethrin, although they have been observed more bands (isoenzymes) in field populations when compared to the susceptible strain Rockefeller, submitted to the pyrethroid insecticide. In this case, there is possibility of esterases are being regulated by a genetic mechanism that insecticide occurs in the presence of preferential activation of certain isoenzyme form.The presence of Kdr mutation was found in all populations studied, and the Praça 14 population was the one with the highest frequency (0.98) and the Monte das Oliveiras, the lowest (0.58). The X2 values for the four populations were not significant, indicating that they are in Hardy-Weinberg equilibrium, with an excess of heterozygotes interpopulation and moderate genetic differentiation, and Praça 14 and the Monte das Oliveiras populations, the most distant genetically. The presence of the mutation Val1016Ile in all populations analyzed suggests that the use of pyrethroids is exposing populations to intense selection pressures. Thus, it is necessary to review the measures used for vector control, as well as the substitution of alternative insecticides deltamethrin by, making sure that the susceptibility is constantly monitored to ensure population control of this vector. Keywords: Aedes aegypti – resistance – organophosphates – pyrethroids – Kdr (Resistance)